Kualitas Proses Pembelajaran dan Motivasi Belajar Siswa pada Materi Ikatan Kimia dengan Pembelajaran Inkuiri Terbimbing Berbantuan Representasi Mikroskopik - Hendrawani, Hendrawani; Subandi, Subandi; Fajaroh, Fauziatul (Jurnal Ilmiah IKIP Mataram, 2020)
This paper reports the effect of microscopic representation through guided inquiry learning upon the quality of learning process and the difference level of studentsâ€™ learning motivation in chemical bonding learning of 10th year of science students of SMAN 1 Gunungsari, West Lombok.Â The research design was quasy experimental design. The subject was 10thÂ year of science students of SMAN 1 Gunungsari, consist ofÂ 3 class, and 30 person in each class. Reseach result shows that:1)The quality ofÂ learning process from the highest areÂ in microscopic representation through guided inquiry learning class, inquiry learning without microscopic representation, and expository class. 2) studentâ€™s learning motivation in microscopic representation through guided inquiry learning class has the highest learning motivation, and the group taught only with guided inquiry learning method without microscopic representation has the higher learning motivation than the group taught in expository class.